Reflection of Verbal Violence in Farrokhi Yazdi's Poems: An Analysis Based on Malkin’s Approach - Arefeh Taherian; Hossein Razavian; Ali Mohammad Shahsani; Esmat Esmaeili (مطالعات زبانی و بلاغی)
In the period of Persian literature, the poetry of the constitutional period is more than ever mixed with political themes, and political themes can be a proper basis for any kind of violence, including verbal violence. Farrokhi Yazdi is one of the prominent poets of this period who is a good example for studying verbal violence. Malkin (2004) is one of the scholars who have addressed the issue of violence in language. He introduces six patterns to illustrate how violence in language occurs, in which language provides a framework for the speaker to apply violence according to these patterns. In this article, we discuss how violence is manifested in 10 poems by Farrokhi Yazdi according to the discourse approach of Malkin (2004). Our criterion for choosing these poems was that Farrokhi used violent words and a violent tone more than any other in his poems. According to the results of this study, Farrokhi Yazdi has used the second pattern more than any other pattern of violence. According to this pattern, language can be a tyrannical weapon of domination and destruction. Frequent use of violent words by Farrokhi has made the second pattern more frequent than other templates. Farrokhi has used pattern number 5 less than the rest of the patterns. According to the fifth pattern, language can embrace and control power. This pattern, which examines the reflection of ideology in language, has been used less frequently in selected poems.